Reduced anisotropy in the middle cerebellar peduncle in Chiari-II malformation - Herweh, Christian; Akbar, Michael; Wengenroth, Martina; Heiland, Sabine; Bendszus, Martin; Stippich, Christoph (The cerebellum, 2010)
Besides supratentorial abnormalities, spina bifida menigomyelocele (SBM) is typically associated with Chiari-II malformation comprising a small cerebellum, which herniates downward due to a shallow posterior fossa. We used diffusion tensor imaging to probe additional microstructural alterations of the major cerebellar white matter tracts, the cerebellar peduncles. A region-of-interest approach was employed in six SBM patients and six matched controls to compare the fractional anisotropy (FA) within the superior, middle, and inferior cerebellar peduncle (SCP, MCP, and ICP, respectively). The FA in the MCP was significantly reduced in the SBM patients (0.44 vs. 0.65, p = 0.002), while there was no significant difference in the other cerebellar peduncles. In the context of numerous supratentorial white matter abnormalities in SBM such as callosal dysplasia, the most likely explanation of reduced FA in the MCP is a reduced fiber density.
Gesehen am 10.05.2023